Complete mitochondrial genome of Allognosta vagans (Diptera, Stratiomyidae) - Qingxia Zhou; Shuangmei Ding; Xin Li; Tingting Zhang; Ding Yang (Mitochondrial DNA. Part B. Resources, 2017)
The complete mitochondrial genome (mitogenome) of Allognosta vagans (Loew, 1873) has been reported in this study. This is the first sequenced mitogenome of the subfamily Beridinae. The genome is 15,982 bp in length, including 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNAs, and a partial sequence of the AT-rich region, and the AT-rich region contains several characteristic repeated sequences. In addition, the nucleotide composition of the coding region was 38.8% of A, 38.7% of T, 9.4% of C, 13.1% of G, 77.5% of A + T content. So far, five complete mitochondrial genome data of related species are available in our lab, all of them are used in Maximum Likelihood and Neighbour-Join analyses. The result supported that Xylomyidae and Stratiomyidae are sister group.